GAGASAN PERLUASAN LEGAL STANDING DALAM PERMOHONAN PEMBUBARAN PARTAI POLITIK DI INDONESIA - Sukroni, Muhammad; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Indonesia is a democratic country whose sovereignty of the people, it has been set out and defined in the Constitution of the Republic of Indonesia in 1945, but people can use their sovereignty to entrust a representative to sit in the seat of government through elections. Elections are conducted by political parties as participants.Political Parties in Indonesia not everything goes according to the rules, of course there are also violations committed by political parties. Against violations of the political party is the government only Yeng entitled to apply to the dissolution of the Constitutional Court. Why do people not involved in the dissolution of political parties? Heres what the author discussed in this thesis research.This study aims to find out why the government just get legal standing in the filing of the dissolution of political parties as well as what if the community is also involved in legal satanding and how efforts to do so that people can also be involved in the dissolution of political parties.The data collection was done by means of data collection study literature relevant to this study in the library and to identify the data or existing cases.Materials collected are from legislation, related books and journals. The acquired data will be analyzed by inductively qualitatively to arrive at a conclusionThe results of this study is the government as the sole applicant filing dissolution of political parties for the sake of the party avoid unhealthy competition, and the author hopes that the community be the applicant is also in accordance with the principle of popular sovereignty and human rights.keywords: folk, dissolution of political parties, the legal standing.